IMPLEMENTASI METODE WP PENILAIAN KINERJA GURU DALAM KEGIATAN SUPERVISI PEMBELAJARAN DI SMK SWASTA AL FURQON BATU BARA - Zuriana, Zuriana; Handayani, Masitah; Sudarmin, Sudarmin (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
Al Furqon Batu Bara Private Vocational School is a private school institution located in Batu Bara Regency which consists of 12 teachers. This school has quite complete facilities and is supported by quite complete technological facilities and information systems. Al Furqon Batu Bara Private Vocational School is also included in the model SMK for other schools, because Al Furqon Batu Bara Private Vocational School has many achievements in various fields. Every year, the Principal conducts an assessment of teacher performance in supervision activities to improve quality education. This method aims to determine the level of achievement of teachers in the school. The Teacher Performance Assessment is not only to determine the level of achievement of teachers in the school, but will also be included in the selection of outstanding teachers which is routinely held by the Ministry of Education and Culture starting at the District, Regency/City, Provincial and National levels. However, the problem with determining Teacher Performance Assessment at Al Furqon Batu Bara Private Vocational School is that it is still subjective in the sense that the assessment is carried out conventionally using assessment sheets because there are no assessment aspects used in assessing teacher performance in supervision activities